PENGARUH QUALITY OF WORKLIFE DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (STUDI KASUS CV RGR INDRAKO SWALAYAN TELUK KUANTAN ) - Marcella Martarina; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to identify and analyse the factors that cause the deviation of budget with its realisation and investigate and analyse the budget and actual cost of the project in improving the road in Sei. Ara, Inhil.The data obtained directly from the company PT. Gunung Guntur which located in Inhil and analysed using analysis of variance, which the authors compare between the actual cost with the standard cost will result the deviation. This analysis is used in order to observe the elements of the project cost budget such as the cost of raw materials, labour costs, and overhead costs.The results of the research concluded that the budget which made by the company PT. Gunung Guntur yet fully functioning properly because the company only sets the standard for the cost of materials and the cost of labours, and the opposite, in budgeting, the overheads cost experienced a lot of adverse deviations (Unfavorable).Keywords: Budget, Actual, Variance